The Agile Supply Chain: Competing in Volatile Markets. - Christopher, Martin (Elsevier, 2000)
Turbulent and volatile markets are becoming the norm as life cycles shorten and global economic and competitive forces create additional uncertainty. The risk attached to lengthy and slow-moving logistics “pipelines” has become unsustainable, forcing organizations to look again at how their supply chains are structured and managed. This paper suggests that the key to survival in these changed conditions is through “agility,” in particular by the creation of responsive supply chains. A distinction is drawn between the philosophies of “leanness” and “agility,” and the appropriate application of these ideas is discussed.